(untitled) (Proceedings of the International Conference on Public Health, 2019)
Cesarean section is an important indicator of accessibility to the emergency obstetric care. The study aims to examine urban-rural inequality and determinant of caesarean section in Indonesia. Cross-sectional data from national household health survey (RISKESDAS) conducted in 2013 were used. A total of 49,045 aged 15-49 years having live births in the last 3 years preceding the survey was included into the analysis. We report absolute difference and ratio of caesarean rates between urban and rural for each province. The logistic regressions were used to identify determinant of caesarean section. The caesarean section rates in rural and urban were 5.4% and 13.4%; respectively. Province estimates of caesarean section rates were ranging from 3.1% in Southeast Sulawesi to 19.1% in DKI Jakarta. Sub-national inequality between urban and rural among province occurs, accounted for absolute difference between -0.2% (West Papua) to 16.2% (Gorontalo). The logistic regression indicates determinant of caesarean section includes older ages, higher education level, currently employed, living in urban area, living in rich household, had any complication during pregnancy, first child, post-term pregnancy and twin had higher caesarean section rates. This study provides evidence that sub-national inequalities of caesarean section rates between urban and rural in Indonesia remain. These inequalities might due to inadequate access to emergency obstetric care among rural subgroups. Sub-national specific intervention among rural population is deeded to address these inequalities.